Difference and Conflict in Global Citizenship in Higher Education in Canada. (1st September 2009) - Andreotti, Vanessa; Jefferess, David; Pashby, Karen; Rowe, Cash; Tarc, Paul; Taylor, Lisa
This paper presents a multi-voiced response to the question: how might conflict and difference be conceptualised in global citizenship education (GCE) imaginaries in Canada? It offers responses from six educators engaged with GCE research and practice in higher education institutions in Canada. The responses address different angles and issues related to difference and GCE, such as multiculturalism, (neo) colonialism, paternalism, indigeneity, internationalism, neoliberalism, benevolence and national identity building in Canada.